Underdevelopment in Spanish America : an interpretation - Griffin, Keith B. (London : George Allen and Unwin, 1969)
This book examines the causes of underdevelopment with specific reference to nine Spanish-speaking countries of South America (Venezuela, Colombia, Ecuador, Peru, Bolivia, Chile, Argentina, Paraguay and Uruguay) and possible measures that could be adopted to accelerate the pace of social and economic progress. It consists of an interpretation of economic backwardness in the Spanish speaking countries of South America, an analysis of the forces restraining progress and suggestions for a development strategy which would combine growth with equity.
Includes bibliographical references and index.
lje 03/10/2018
Loans
Keywords: Economic development; Regional integration; International Trade; Inflation; Exchange rate; Foreign investments; Capital imports; Exports; Latin America